Weight Loss - Jáuregui Lobera, Ignacio (IntechOpen, 2018)
Epidemiological studies show that weight loss has many health benefits, so different strategies have been explored to lose weight, with health and esthetic reasons being the base of those strategies. Weight loss may be the result of pathologies, so both intentional and unintentional weight loss are different situations, each being a relevant focus of study. Along with that distinction, gender and ethnic topics are also relevant aspects, and different chapters of this book are related to male vs. female topics as well as to cultural differences related to weight loss. Childhood obesity from a parenting style perspective is also developed in this book. Finally, it must be noted that activity is essential to improve body composition and also to keep an ideal weight.